Comparative thought Ian A Fazlur Rahman and M. Syafii Amtonio about Bunga Bank - Ambo Dalle Bohari; Syarifudin Syarifudin (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
The study, titled "Comparative thought Ian A Fazlur Rahman and M. Syafii Amtonio about Bunga Bank," aims to describe the figure's thinking about the bank's interest. According to A Fazlur Rahman looked to allow interest of the bank and did not equate with RIBA, and according to Muhammad Syafi'i Antonio looked at the bank interest of something unclean and equally legal with RIBA, that is equally haram. This type of research is a library research, which is research that makes the literature as the main source (data). The nature of this research is A comparative-comparatively describing the thought of A. Fazlur Rahman and Muhammad Syafi'i Antonio systematically and as objectively as possible.  The equation is not found in this study because the scholarly study was different. The difference is, A Fazlur Rahman does not agree if bank interest includes RIBA. Thus, it does not reject the elimination of bank interest in Pakistan on the grounds of economic development, although it includes the peace. To justify the bank's interest (RIBA) although it is not a threat of unrest and exploitative, different. While Muhammad Syafi'i Antonio argued that bank interest as something unlawful because bank interest is a principal loan burden to be paid at maturity, even if the effort or project suffered losses. So the borrower feels burdened with the increase in interest of the bank.